2007
DOI: 10.1136/gut.2006.113431
|View full text |Cite
|
Sign up to set email alerts
|

Faecal S100A12 as a non-invasive marker distinguishing inflammatory bowel disease from irritable bowel syndrome

Abstract: Objective: S100A12 is a pro-inflammatory protein that is secreted by granulocytes. S100A12 serum levels increase during inflammatory bowel disease (IBD). We performed the first study analysing faecal S100A12 in adults with signs of intestinal inflammation. Methods: Faecal S100A12 was determined by ELISA in faecal specimens of 171 consecutive patients and 24 healthy controls. Patients either suffered from infectious gastroenteritis confirmed by stool analysis (65 bacterial, 23 viral) or underwent endoscopic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
152
5
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(174 citation statements)
references
References 60 publications
15
152
5
2
Order By: Relevance
“…82 However, both markers show correlation with endoscopic and histological inflammation. 183,184 The reported ranges for sensitivity with S100A12 are 86-97%) and specificity 92-100%. 82,183,184 The cut-off most commonly used was 10 µg/g.…”
Section: S100a12mentioning
confidence: 99%
See 1 more Smart Citation
“…82 However, both markers show correlation with endoscopic and histological inflammation. 183,184 The reported ranges for sensitivity with S100A12 are 86-97%) and specificity 92-100%. 82,183,184 The cut-off most commonly used was 10 µg/g.…”
Section: S100a12mentioning
confidence: 99%
“…183,184 The reported ranges for sensitivity with S100A12 are 86-97%) and specificity 92-100%. 82,183,184 The cut-off most commonly used was 10 µg/g. However, it should be noted that, unlike calprotectin, most of the studies performed on S100A12 were in children and on a much smaller data set.…”
Section: S100a12mentioning
confidence: 99%
“…[49][50][51][52] However, most studies found no difference in the faecal levels of calprotectin and lactoferrin between IBS patients and healthy controls. 43,44,49,50,[52][53][54][55][56][57][58][59] Only one publication reported that increased levels of faecal calprotectin were correlated with pain severity; however, this result was observed in children displaying both functional abdominal pain and IBS. 60 Key point: (i) Typically, no changes in the levels of the faecal inflammatory markers calprotectin and lactoferrin are reported in IBS patients.…”
Section: Key Pointsmentioning
confidence: 99%
“…The mRNAs correspond to a panel of pro-inflammatory host proteins (IL-1β, IL-6, IL-8, calprotectin and osteoprotegerin (OPG)), which are found in excess in the stool in infectious or inflammatory diarrhea by EIA, or have been found to be associated with the intestinal immune response to infection. [6][7][8][9][10][11] We also compared the resulting transcript ratios to protein concentrations as determined by EIAs for IL-8, calprotectin and OPG. …”
Section: Introductionmentioning
confidence: 99%